KORELASI KONTROL DIRI DENGAN PERILAKU AGRESIF PADA REMAJA LAKI-LAKI PEMINUM MIRAS (Studi Kontekstual Pada Remaja Di Jemaat GPM Imanuel OSM- AMBON) - Salomina Patty; Prisca Diantra Sampe (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2018)
The study aims to know empirically the relationship between self control and the aggressive behavior of young male drinkers. The hypothesis that researchers ask is that there is a negative connection between self-control and aggressive behaviour in adolescent male-drinkers. The better the self-control in adolescent male drinkers, the lower the aggressive behavior, and vice versa. The subject in this study amounted to 72 teenage men of alcohol drinkers with characteristics aged 15-21 years and consumed a minimum of miras already 2 months. The sampling techniques used are purposive sampling techniques.The study used the aggressive behavior scale on adolescent male liquor and self-control scales in data retrieval. Data analysis is done using the correlation technique of Product Moment.Â Â  The results showed that there was a negative link between aggressive behavior in adolescent male drinkers with self control with rxy values =-0.497 and (P < 0.01), so hypotheses in this study were accepted.Keyword: aggressive behaviour in adolescent male drinkers, self control